Attachment styles, self‐compassion, and psychological adjustment in long‐term breast cancer survivors. Issue 5 (11th April 2019) - Arambasic, Jelena; Sherman, Kerry A.; Elder, Elisabeth; ,
Abstract: Objective: The increasing numbers of breast cancer survivors highlight the importance of delineating factors that identify women who are at risk of poor psychological adjustment in the long term. In breast cancer survivors, higher attachment anxiety and attachment avoidance have been associated with poorer psychological adjustment. Moreover, there is evidence that self‐compassion, a kind manner of treating oneself during difficulties, is associated with psychological adjustment in this population. This study aimed to extend the association between attachment styles and psychological adjustment to the context of long‐term breast cancer survivors and to determine whether lower self‐compassion underlies this association. Methods: Participants (N = 82) were recruited through emailed invitations to members of the Review and Survey Group of Breast Cancer Network Australia. Following online consent, participants completed measures assessing attachment styles, self‐compassion, psychological stress, and the perceived negative impact of cancer. Bootstrapping analyses using the PROCESS macro were used to test the significance of indirect effects. Results: As hypothesised, correlational analyses revealed that higher attachment anxiety and attachment avoidance were significantly and positively associated with stress and perceived negative impact of cancer. Bootstrapping analyses revealed significant indirect effects of attachment anxiety and attachment avoidance (on both stress and perceived negative impact of cancer) through lower self‐compassion. Conclusions: These findings suggest that self‐compassion training may be useful for enhancing the psychological adjustment of long‐term breast cancer survivors. Future longitudinal and experimental studies in more diverse samples are needed to confirm causal directionality of these relationships and to expand upon these findings.